Hydrogeochemical conditions of formation of dawsonite mineralization in the Berezovoyarka area, Kuznetsk Basin; Geochemistry International; Vol. 42, N 10 - Shvartsev S. L. Stepan Lvovich (2004, 2004)
В фонде НТБ ТПУ отсутствует